The role of oxidative stress and antioxidant supplementation in pregnancy disorders - Poston, Lucilla; Igosheva, Natalia; Mistry, Hiten D.; Seed, Paul T.; Shennan, Andrew H.; Rana, Sarosh; Karumanchi, S. Ananth; Chappell, Lucy C. (American Society for Nutrition, 2011)
Oxidative stress is widely implicated in failed reproductive performance including infertility, miscarriage, diabetes-related congenital malformations and preeclampsia. Maternal obesity is a strong risk factor for preeclampsia, and recently, in an animal model of maternal obesity we have reported evidence of oxidative stress in the oocytes of obese animals prior to pregnancy as well as in early stage embryos. This adds to the growing evidence for a greater focus on the pre-conceptual period in prevention of pregnancy disorders including those related to oxidative stress. Our research has also focussed on the role of free radicals and antioxidant capacity in preeclampsia. Assessment by measurement of markers of lipid peroxidation or of antioxidant capacity has provided unequivocal evidence for oxidative stress in this disorder. Partial failure of the process of placentation has been implicated, with recent evidence proposing that ischaemia-reperfusion in the placenta may contribute to oxidative stress in trophoblast. Endoplasmic reticulum stress in the placenta may also play a role. We and others have performed randomised controlled trials to determine whether early supplementation with vitamins C and E in women at risk of preeclampsia may be beneficial but these studies have shown no evidence for prevention of preeclampsia. Whether this represents an inappropriate antioxidant strategy or whether supplementation has been too late in gestation to be beneficial is not known. Other potential approaches to prevention of preeclampsia through amelioration of oxidative stress include provision of supplements in the pre-conceptual period, selenium supplements, anti-peroxynitrite strategies and statins.